(untitled) (Experimental biology, 2017)
The possibility of cleaning contaminated soil test range LLP "Zhyly-Bolashak" active associations oxidizing microorganisms. It is shown that after their introduction into the soil increased the number ofmajor groups of microorganisms. The degree of degradation of oil in one month was 46.9% and 70.8%.